Extraction techniques in analytical sciences. - Dean, John R., ....- (Chichester : Wiley, 2009)
Series Preface. Preface. Acknowledgements. Acronyms, Abbreviations and Symbols. About the Author. 1 Pre and Post-Extraction Considerations. AQUEOUS SAMPLES. 2 Classical Approaches for Aqueous Extraction. 3 Solid Phase Extraction. 4 Solid Phase Microextraction. 5 New Developments in Microextraction. SOLID SAMPLES. 6 Classical Approaches for Solid-Liquid Extraction. 7 Pressurized Fluid Extraction. 8 Microwave-Assisted Extraction. 9 Matrix Solid Phase Dispersion. 10 Supercritical Fluid Extraction. GASEOUS SAMPLES. 11 Air Sampling. COMPARISON OF EXTRACTION METHODS. 12 Comparison of Extraction Methods. RESOURCES. 13 Resources for Extraction Techniques. Responses to Self-Assessment Questions. Glossary of Terms. SI Units and Physical Constants. Periodic Table. General Index. Application Index.